DISPARITAS PEMBANGUNAN EKONOMI ANTAR WILAYAH DI PROVINSI MALUKU UTARA - Aisa ., Mashud; Noortje M. Benu; Mex F. L. Sondakh (Sam Ratulangi University, 2018)
The objective of this research is to assess the economic development disparities among districts and cities in North Maluku in 2010 - 2015 period. This research is motivated by the diversity of natural resources and demographic conditions, differences in income per capita and economic growth contained in each regency and town in North Maluku. As a result of these differences, the ability to increase economic development is different from one region to the other region. The data collected for two months from February to March 2017. The data used are PDRB per capita data, population data and economic growth data obtained from Central Bureau of Statistics of North Maluku Province. Analysis of data in the form of descriptive analysis presented in tabular form using Williamson Index analysis tool. The results showed that the economic development district and cities in the province of North Maluku during the period 2010 - 2015 continues to inequality, where the data is used proved that there are significant differences among the districts and cities in North Maluku. Results proficiency level could be seen clearly when analyzed by Williamson Index which indicates that the rate of economic development was still classified inequality on inequality of economic development. This was due to the diversity of potential and natural resources among districts and cities that led to per capita income and economic growth becomes different resulting imbalance of economic development.